The Potential of Billygoat Weed Leaf Extract (Ageratum Conyzoides) in Increasing Platelet Counts of Male Mice (Mus Musculus) - Velina, Yessy; Diana, Nirva; Annisa, Aulia (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
Billygoat weed (Ageratum conyzoides) is mainly used to treat wounds and fever. People also do not understand the use of these leaves in the treatment to increase the platelet counts. The objectives of this research Objectives were to test whether the Billygoat Weed’s leaves can increase platelet count of male mice and to find out what is the most effective dose of the Billygoat Weed on the platelet count of male mice. This research was done by employing the true experimental approach with the completely randomized design which consisted of 5 treatments, namely the negative control (plain water), the positive control (acetylsalicylic acid), 1.68 mg/kgBW, 2.52 mg/kgBW, and 3.36 mg/kgBW on five mice in each treatment. The increase in the platelet counts, based on the results of One-Way ANOVA with a p-value of 0,0004, the Billygoat Weed extract was able to increase the platelet counts. Through further testing, the smallest significant difference showed that a dose of 3.36 mg/kgBW was effectively able to increase the platelet counts of male mice with an average of 11140.80/. Billygoat weed (Ageratum conyzoides) is mainly used to treat wounds and fever. People also do not understand the use of these leaves in the treatment to increase the platelet counts. The objectives of this research Objectives were to test whether the Billygoat Weed’s leaves can increase platelet count of male mice and to find out what is the most effective dose of the Billygoat Weed on the platelet count of male mice. This research was done by employing the true experimental approach with the completely randomized design which consisted of 5 treatments, namely the negative control (plain water), the positive control (acetylsalicylic acid), 1.68 mg/kgBW, 2.52 mg/kgBW, and 3.36 mg/kgBW on five mice in each treatment. The increase in the platelet counts, based on the results of One-Way ANOVA with a p-value of 0,0004, the Billygoat Weed extract was able to increase the platelet counts. Through further testing, the smallest significant difference showed that a dose of 3.36 mg/kgBW was effectively able to increase the platelet counts of male mice with an average of 11140.80/??3.